2005
DOI: 10.1258/0022215054273223
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral objective tinnitus secondary to congenital middle-ear myoclonus

Abstract: Subjective tinnitus (heard only by the patient) is a common otological complaint. Objective tinnitus (heard by the examiner as well as the patient) is extremely rare. There are only a few cases of objective tinnitus, secondary to middle-ear myoclonus, described in the literature. We present the case of a child with bilateral, congenital, objective tinnitus, secondary to middle-ear myoclonus, with otherwise normal hearing thresholds (250 Hz-8 kHz), and with no evidence of intra-cerebral or systemic disorders. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 5 publications
0
12
0
2
Order By: Relevance
“…There have been several case reports showing outcomes following tendon resection for MEMT [Abdul-Baqi, 2004;Cohen and Perez, 2003;Howsam et al, 2005;Zipfel et al, 2000], and most of these case studies reported full resolution of the symptoms after surgery. To the best of our knowledge, this study reports the results of the largest case series of METR which demonstrates convincing results of this surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several case reports showing outcomes following tendon resection for MEMT [Abdul-Baqi, 2004;Cohen and Perez, 2003;Howsam et al, 2005;Zipfel et al, 2000], and most of these case studies reported full resolution of the symptoms after surgery. To the best of our knowledge, this study reports the results of the largest case series of METR which demonstrates convincing results of this surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to vascular anomalies (Chandler, 1983), vibrations due to pulsatile blood flow near the middle or inner ear (Weissman and Hirsch, 2000;Liyanage et al, 2006;Sonmez et al, 2007) can become audible. Also, involuntary contraction of muscles in the middle ear (Abdul-Baqi, 2004;Howsam et al, 2005) or in palatal tissue (Fox and Baer, 1991) may cause objective tinnitus. Objective tinnitus is rare and has been described only in case reports.…”
Section: Tinnitus Definition and Prevalencementioning
confidence: 99%
“…Muscular tinnitus is another cause. It has two forms: middle ear tinnitus and palatal myoclonus, both of which are associated with rhythmic contractions of muscles around the skull base and may produce objective tinnitus [44]. A patulous Eustachian tube may produce a variety of extraneous sounds [8].…”
Section: Diseases Without Radiologic Manifestationsmentioning
confidence: 99%